Faktor Pendorong dan Penghambat Keberhasilan Pengadaan Tanah Skala Kecil di Kabupaten Karanganyar (Studi Pembangunan Sistem Penyediaan Air Minum Regional WOSUSOKAS dan Jembatan Kragan) - Annis Naryana; Sudibyanung Sudibyanung; Sukmo Pinuji (Sekolah Tinggi Pertanahan Nasional, 2020)
Abstract: The study aims to determine the implementation of small–scale land procurement for development in Karanganyar Regency and to find out the factors that encourage and hinder the successful implementation of small–scale land procurement, especially for development in Karanganyar Regency. The research method is a qualitative method with a descriptive approach. Data collection techniques used in this study was: interviews and documentation. The results of the study indicate that the mechanism for small–scale land procurement for development for the implementation of small–scale land procurement is only an agreement with landowners. The factors that drive the success of the implementation of small–scale land procurement, especially for development in Karanganyar Regency are: a) Arrangements regarding planning for small–scale land procurement indicate that the nature of planning and preparation in the land procurement stage is a synchronization stage between development needs with the location where the land was procured. b) Public consultation and socialization are very important stages and must be carried out according to the provisions. The factors that hinder the success of the implementation of small–scale land procurement, especially for development, are determining the price of land to be purchased by agencies that need land. The strategy for overcoming the inhibiting factors for the successful implementation of small–scale land procurement, especially for development in Districts of Karanganyar, is that the relevant agencies carry out deliberations on compensation pricing with village officials and the community until a price agreement is found. Keywords: driving, inhibiting, small–scale land procurement Intisari: Tujuan penelitian untuk mengetahui pelaksanaan pengadaan tanah skala kecil untuk pembangunan di Kabupaten Karanganyar dan mengetahui faktor yang mendorong dan menghambat bagi keberhasilan pelaksanaan pengadaan tanah skala kecil khususnya untuk pembangunan di Kabupaten Karanganyar. Metode penelitiannya adalah metode kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa mekanisme pengadaan tanah skala kecil untuk pembangunan dilakukan dengan tahapan perencanaan, persiapan, pelaksanaan dan penyerahan hasil. Faktor–faktor yang mendorong bagi keberhasilan yaitu: a) Pengaturan mengenai perencanaan pengadaan tanah untuk skala kecil. b) Konsultasi publik dan sosialisasi merupakan tahap yang sangat penting dan wajib dilaksanakan sesuai ketentuan. Faktor–faktor yang menghambat yaitu penentuan harga tanah yang akan dibeli oleh instansi yang membutuhkan tanah. Strategi untuk mengatasi faktor penghambat keberhasilan pelaksanaan pengadaan tanah skala kecil yaitu instansi terkait melaksanakan kembali musyawarah penetapan harga ganti kerugian dengah para aparat kelurahan dan masyarakat hingga ditemukan kesepakatan harga. Kata Kunci: pendorong, penghambat, pengadaan tanah skala kecil